The Synergy of Strategic Orientations and Competitive Advantage in Enhancing MSME Marketing Performance - Solechan, Achmad; Wardhani, Arisanti Ayu; Shibghatalloh, Ahmad Hafiyyan; Syafrudin, Hasan Aminda (Equator Journal of Management and Entrepreneurship (EJME), 2026)
This study analyzes the influence of entrepreneurial orientation, digital marketing orientation, and innovation orientation on competitive advantage and marketing performance in micro, small, and medium enterprises (MSMEs) in Central Java, Indonesia. Using the SEM-PLS method, data were collected from MSME owners who have adopted digital marketing. The results show that entrepreneurial orientation and digital marketing orientation enhance competitive advantage, which in turn positively impacts marketing performance. However, innovation orientation, although positively contributing to competitive advantage, does not have a significant direct effect on marketing performance. Competitive advantage plays an important role as a mediator between strategic orientation and marketing performance. These findings enrich the strategic management literature by clarifying the still inconsistent role of innovation orientation in MSME performance. Practically, this study recommends that MSME owners and policymakers prioritize entrepreneurial activities and digital strategies to enhance competitiveness and marketing success in a dynamic business environment.